Banjir di perkotaan dan dampaknya bagi masyarakat: Studi fenomenologi - Yuriadi, Yuriadi; Bathasya Thory Rahmadhany; Agnesya Dwi Septya Yudha; Alvin Syawaludin Mulyono (INNER: Journal of Psychological Research, 2025)
The phenomenon of flooding is a concern for everyone, as many people still lack awareness about disposing of waste properly. Furthermore, inadequate drainage means that water volume cannot be properly accommodated. The purpose of this study is to raise awareness, establish regulations, and create new habits. The method used in this research is qualitative. The study found that flooding occurs due to many factors, including a lack of awareness about disposing of waste properly and regulations regarding waste disposal. Furthermore, it is necessary to create new habits that can change people’s waste disposal practices and their perspectives on disposing of waste properly. Low awareness of maintaining environmental cleanliness and a lack of waste management facilities are the main factors causing flooding. Residents also recognize that household waste disposed of in rivers and gutters clogs waterways, preventing rainwater from flowing smoothly and ultimately overflowing into residential areas. Keywords: phenomenon, flood, waste, environment, residential areas